Healthcare professionals knowledge of autism spectrum disorders - Karolina Juraszek; Zdzisława Kalisz; Anna Maszudzińska; Magda Kucharczuk; Justyna Kalisz (Kazimierz Wielki University, 2019)
Introduction: Autism spectrum disorders (ASD) is a diverse group of neurodevelopmental disorders, which belongs to the most frequent child developmental problems. It characterized by different levels of functioning of persons who has this disorder, showing impaired social interaction, impaired communication, and restricted and repetitive behavior. What is more, there is likelihood of occurring other disorders. Particularity of ASD, the difficulties in diagnosing cause that the person has frequent contact with medical personnel. The patient with ASD is special patient, presenting atypical behaviors and reactions, due to the different reception of the surrounding reality. He requires from health care practitioners to adopt an individual approach and special treatment based on knowledge about the specificities of autism spectrum disorders and professional competence. The aim of a study: Determining the level of knowledge of health care professionals on autism spectrum disorders. The factors which influence on the level of their knowledge were the subject of thorough statistical analysis. In addition, the views of medical personnel on the individual treatment of autistic persons in their work and the impact of the level of knowledge declared on the treatment of ASD patients were analyzed. Material and methods: 122 health workers took part in the study in the Regional Specialist Hospital in Grudziadz: doctors, nurses / midwifes and registrants / medical secretaries. Results: The research shows that the level of knowledge of health care workers on ASD disorders is low. The best performers were doctors, then nurses/midwives and finally medical recorders/ secretaries. Despite low levels of knowledge, medical professionals do not participate in specialist courses and fewer than half of the subjects are knowledgeable about ASD. At the same time they are convinced of the need for special treatment of autistic patients, but not taking them out of que. Conclusions: Improving the knowledge of health professionals on autism spectrum disorders by increasing knowledge, attending conferences and the courses and experience of caregivers and professionals dealing with ASD patients will have a beneficial effect on the health and well-being of patients while providing health services, which will significantly improve the quality of services provided.